The effect of heat treatment on mechanical properties of spring steel - Kurt, Emre. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Springs are mechanical elements that exert forces or torques and absorb energy. The absorbed energy is usually stored and later released. Steel springs are made in many types, shapes, and sizes, ranging from delicate hair-springs for instrument meters to massive barrel springs for railroad equipment. In the automotive industry springs are used in many applications. DIN 50CrV4 or AISI 6150 spring steel is widely used as a spring material in this industry. It is a high-carbon chromium-vanadium alloy steel which has been used for numerous applications including premium quality springs. Also, microalloying is applied to 50CrV4 to improve its mechanical properties. In present study, the effect of heat treatment on mechanical properties of spring steel was investigated. Two different 50CrV4 alloys, one is microalloyed with Ti, were austenitized at 910 °C, then oil quenched. Finally, they were tempered at two different tempering temperatures, 410 °C and 440 °C. Their microstructures, and mechanical properties such as hardness, tensile, impact, and fatigue properties were determined and compared. From the specimens, fully temperedmartensitic microstructures were obtained having hardness values range from 460 to 497 HB. Their tensile strengths range from 1585 to 1696 MPa while their fatigue limits range from 870 to 950 MPa. Fatigue tests were performed on a specially set rotating bending fatigue test machine. As a result of the impact test, it was found out that all the specimens were very brittle. Moreover, when we examined the fracture appearance of the impact test specimens, the increase in cleavage area in both two steel alloys could be observed by the decrease in tempering temperature.
Keywords: Springs (Mechanism)